The Veterans Affairs Neuropathy Scale: A Reliable, Remote Polyneuropathy Exam - Wilson, Andrew M.; Ong, Michael K.; Saliba, Debra; Jamal, Nasheed I. (Frontiers in Neurology, 2019)
Introduction Polyneuropathy (PN) complaints are common, prompting many referrals for neurologic evaluation. To improve access of PN care in distant community clinics, we developed a telemedicine service (patient-clinician interactions using real-time videoconference technology) for PN. The primary goal of this study was to construct a remote exam for PN that is feasible, reliable, and concordant with in-person assessments for use in our tele-PN clinics. Methods To construct the VA Neuropathy Scale (VANS), we searched the literature for existing, validated PN assessments. From these assessments, we selected a parsimonious set of exam elements based on literature-reported sensitivity and specificity of PN detection, with modifications as necessary for our teleneurology setting (i.e., a technician examination under the direction of a neurologist). We recruited 28 participants with varying degrees of PN to undergo VANS testing under 5 scenarios. The 5 scenarios differed by mode of VANS grading (in-person vs. telemedicine) and by the in-person examiner type (neurologist vs. technician) in telemedicine scenarios. We analyzed concordance between the VANS and a person’s medical chart-derived PN status by modeling the receiver operating characteristic (ROC) curve. We analyzed reliability of the VANS by mixed effects regression and computing the intraclass correlation coefficient (ICC) of scores across the 5 scenarios. Results The VA Neuropathy Scale (VANS) tests balance, gait, reflexes, foot inspection, vibration, and pinprick. Possible scores range from 0 to 50 (worst). From the ROC curve, a cutoff of >2 points on the VANS sets the sensitivity and specificity of detecting PN at 98% and 91%, respectively. There is a small (1.3 points) but statistically significant difference in VANS scoring between in-person and telemedicine grading scenarios. For telemedicine grading scenarios, there is no difference in VANS scores between neurologist and technician examinations. The ICC is 0.89 across all scenarios. Discussion The VANS, informed by existing PN instruments, is a promising clinical assessment tool for diagnosing and monitoring the severity of PN in telemedicine settings. This pilot study indicates acceptable concordance and reliability of the VANS with in-person examinations.